1990
DOI: 10.1152/jappl.1990.68.6.2527
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative phosphorylation system during steady-state hypoxia in the dog brain

Abstract: The relationship between biochemical and physiological responses and tissue O2 during hypoxia was investigated in vivo in the dog brain by 31P nuclear magnetic resonance (NMR) spectroscopy. Our findings demonstrate how ATP synthesis in the brain can be maintained during hypoxia because of compensatory changes in NADH, ADP, and Pi. Eleven beagle dogs were anesthetized and mechanically ventilated, and a steady-state graded hypoxia was induced by decreasing the fraction of inspired O2 (FIO2) stepwise at 20-min in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 0 publications
6
26
1
Order By: Relevance
“…Since NADH concentration in brain is normally 50 times higher than the Km for NADH (10 uM), this term in equation (2) is negligible and can be ignored (Nioka et al, 1990(Nioka et al, ,1991. Similarly, we have assumed that before injury there is no oxygen limitation and that oxygen concentration is far in excess of its Km (0.1 |iM), thereby effectively eliminating this term from the equation.…”
Section: Discussionmentioning
confidence: 99%
“…Since NADH concentration in brain is normally 50 times higher than the Km for NADH (10 uM), this term in equation (2) is negligible and can be ignored (Nioka et al, 1990(Nioka et al, ,1991. Similarly, we have assumed that before injury there is no oxygen limitation and that oxygen concentration is far in excess of its Km (0.1 |iM), thereby effectively eliminating this term from the equation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that cerebral oxygen delivery is maintained over several hours of exposure to hypoxia in humans (Wolff 2000) and in animals (Nioka et al 1990). During 30 minutes of acute 12.5% hypoxia we observed no significant decrease in cerebral oxygen delivery to either white matter or grey matter regions, indicating that cerebral oxygen delivery is maintained during the acute-phase response to acute hypoxia as well.…”
Section: Acute-phase Hemodynamic Response and O 2 Deliverymentioning
confidence: 99%
“…ATP, ADP, and AMP do not change unless the PaO 2 is Ͻ25 mm Hg, whereas phosphocreatine, NADH redox state, and pH i change at Ͻ35 mm Hg. 52,55 However, the lactate and pyruvate levels begin to increase when the PaO 2 is Ͻ50 mm Hg. This would explain in part why the severely hyperglycemic/moderately hypoxic animals were markedly more acidotic than the severely hyperglycemic/normoxic animals.…”
Section: Moderate Hypoxia/ischemiamentioning
confidence: 99%